Photoinduced Electron Transfer Between Metalloporphyrin Complex Dihydroxy Antimony ( v) Tetrapbenylporphine and Halide in Acetonitrile Solution - .AJ-Agealy, H.J.M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
:Electron transfer (El) through molecular frameworks is. ce.ntral to a wide range of chemical, physical , an biological processes. Atheoretical calculation Â·investigation of (ED between dihydroxy antimony (V) tetraP.henylporphine cation (Sb’’(TP.P)(04)2] and halid cr,BrÂ·,r ,and SCN- is presented . These Calculations &re is fiting on experrnental studies Showing that the rate of Electron Transfer. The theoretical Calculation are based Â·an a eontinm: m theory. The tran:sferr ng is treated quantum mechanically, and the solvent iÂ·s represented as adielectric continuum . For electronically nonadiabatic ET , the rate expres ions for (ET),KET ,depend on the e1ectronic Coupling matrix element ,HAB , the free energy change of the reaction !:!..G o â€¢ and the reorganization energy J.